Makespan optimization using Timed Petri Nets and Mixed Integer Linear Programming Problem. Issue 4 (2020) - Marino, E. Di; Su, R.; Basile, F.
Abstract: In this paper, a method for generating a mixed integer linear programming problem from deterministic timed Petri nets to optimize the makespan of manufacturing systems is proposed. After exposing several challenges involved in such a model transformation, a novel method is exploited to overcome them. The adopted solution may create a synergy between the highly expressive timed Petri net modelling framework and the computational attractive mathematical programming tool set.